Analysis Of The Perceptions State University of Medan Students About Scatter (Online Gambling) - Cindy Aulia Rusli; Dilla Ayu Kartika; Muhammad Reynal; Yuliana Dewi Siregar; Rizka Harianingsih; Hapni Laila Siregar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The current era of globalization has many impacts on Indonesian society, including the impact of online gambling addiction. In recent years, gambling over the Internet, or commonly called online gambling, has been increasing. According to Kata data, of the total 2.8 million people involved in online gambling or slots in Indonesia, as many as 2.2 million of them are university students. These people participate in virtual gambling activities through online platforms such as websites and applications connected to the internet. The entire transaction process from depositing to withdrawing gambling winnings is carried out online in an online connected system. The purpose of this study is to analyze the factors that make current students interested in online gambling (scatter). This study uses quantitative research methods with a focus on results. The research data was collected through questionnaires distributed to several respondents who are students. The results showed that the impact of online gambling on students is to cause feelings of laziness and reduce academic performance. On average, students spend up to one hour playing Scatter. Financial difficulties (pocket money) are also a factor that affects students playing scatter (online gambling).